Flexible composite electrode and preparation method and application thereof
By using flexible composite electrodes in perovskite solar cells, modifying materials to improve the interface contact performance between the carbon electrode and the perovskite layer or hole transport layer, the problem of poor interface contact performance is solved, and the battery efficiency and stability is improved. And reduces the preparation cost.
Patent Information
- Application Number
- CN202411225714.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-17
AI Technical Summary
In existing perovskite solar cells, the interface contact between the carbon electrode and the perovskite layer or hole transport layer has poor performance, resulting in low battery efficiency and high cost, and organic solvents can easily destroy the film during the preparation process, affecting the quality of the battery.
Flexible composite electrodes are adopted, including flexible conductive substrates, conductive carbon layers and modified material layers. The modification materials are carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole and polyaniline et al., the organic solvent is removed by coating and heat treatment to improve the interface contact performance.
It significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells, simplifies the preparation process, reduces costs, and is suitable for large-area preparation.
Smart Images

Figure CN119156029A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of thin film solar cell preparation, and specifically relates to a flexible composite electrode and a preparation method and application thereof. Background Art
[0002] Perovskite solar cells (PSCs) are a new type of photovoltaic device that uses lead-halogen semiconductor materials with a perovskite structure as the light-absorbing layer. In 2009, Professor Miyasaka reported the first liquid perovskite solar cell. The birth of solid-state perovskite solar cells in 2012 put the development of perovskite cells on the fast track. After only a dozen years, the conversion efficiency of perovskite cells has approached 27%, making it the new darling in the photovoltaic field. The industrialization of perovskite cells has become an important issue for scientific researchers. The industrialization of perovskite cells needs to meet the three aspects of high efficiency, long life, and low cost (the "golden triangle") at the same time, and also take into account environmental pollution during the preparation process.
[0003] Perovskite cells are divided into two categories: positive cells and reverse cells, each with its own advantages and disadvantages. For positive perovskite cells, the cell efficiency has reached 26%, which is achieved based on gold electrodes. The high cost of gold electrodes has become the most critical factor restricting the further reduction of the cost of positive cells. People have tried various materials to replace Au electrodes. Among them, carbon electrodes replace gold electrodes, which can not only greatly reduce the material cost of the battery, but also in the electrode preparation process, large-scale screen printing or scraping can be used to prepare carbon electrodes, so it can replace the vacuum evaporation method, which is conducive to further reducing production costs.
[0004] Carbon-based perovskite solar cells are usually divided into two categories: those with hole transport layers and those without hole transport layers. Among them, carbon-based perovskite cells with hole transport layers have higher efficiency. However, the efficiency of carbon-based perovskite cells is still lower than that of corresponding metal electrode perovskite cells. The main reason is that the carbon electrode often requires high-temperature treatment to remove excessive organic solvents during the preparation process, which easily leads to poor interface contact performance between the carbon electrode and the perovskite / hole transport layer. In addition, there are a large number of organic solvents in the film preparation process, which can easily damage the perovskite layer and the perovskite / hole transport layer, which will significantly reduce the quality of the film. At present, people are mainly concerned about how to improve the quality of perovskite crystals in carbon-based perovskite cells, but there is little research on the surface interface of the carbon electrode itself.
[0005] The existing technology ignores the study of the interface between the carbon electrode and the perovskite or the interface between the carbon electrode and the perovskite / hole transport layer. In fact, this work has a great impact on improving the open circuit voltage, fill factor and short circuit current of the device.
[0006] Therefore, there is an urgent need for a method for modifying carbon electrodes to improve the performance of the interface. Summary of the invention
[0007] The purpose of the present invention is to provide a flexible composite electrode, which is based on a carbon electrode and introduces a modified material layer on its surface to improve the interface contact performance between the carbon electrode and the perovskite layer or the perovskite layer / hole transport layer, thereby improving the photoelectric conversion efficiency of such batteries.
[0008] Another object of the present invention is to provide a method for preparing the flexible composite electrode of the present invention. The method is simple, easy to operate, suitable for large-area preparation, and has advantages in terms of raw materials and preparation costs.
[0009] Another object of the present invention is to provide an application of the flexible composite electrode of the present invention in a perovskite solar cell. The flexible composite electrode of the present invention improves the efficiency of carbon-based perovskite solar cells, thereby promoting the practical application of such cells.
[0010] The above-mentioned object of the present invention is achieved through the following technical solutions.
[0011] In a first aspect, the present invention provides a flexible composite electrode, comprising:
[0012] Flexible conductive substrate,
[0013] a conductive carbon layer on the flexible conductive substrate; and
[0014] a modification material layer located on the conductive carbon layer;
[0015] Wherein, the modified material layer is composed of one or more materials selected from carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole and polyaniline.
[0016] Preferably, in the flexible composite electrode of the present invention, the thickness of the conductive carbon layer is 1 to 50 μm.
[0017] Preferably, in the flexible composite electrode described in the present invention, the flexible conductive substrate is ITO / PET, ITO / PEN, Ag nanowire / PET, Ag nanoparticle / PET, or carbon nanotube / PET.
[0018] In a second aspect, the present invention provides a method for preparing the flexible composite electrode of the present invention, comprising the following steps:
[0019] (1) coating a carbon slurry on a flexible conductive substrate to obtain a substrate with a carbon slurry coating;
[0020] (2) immersing the substrate with the carbon slurry coating in a first organic solvent to remove the high boiling point solvent in the carbon slurry coating, and obtaining a substrate with a conductive carbon layer after drying;
[0021] (3) coating the modified material dispersion on the conductive carbon layer, and subjecting the obtained structure to a heat treatment to remove all organic solvents, thereby obtaining a flexible composite electrode.
[0022] Preferably, in the method of the present invention, the modifying material dispersion comprises a modifying material and a second organic solvent.
[0023] Preferably, in the method of the present invention, the modifying material is selected from one or more of carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole and polyaniline.
[0024] Preferably, in the method of the present invention, the second organic solvent is selected from one or more of ethanol, methanol, isopropanol and acetonitrile.
[0025] Preferably, in the method of the present invention, the concentration of the modified material dispersion is 0.1-20 mM. In the present invention, the modified material is coated on the surface of the flexible electrode, and since the modified layer is extremely thin, the relative thickness is expressed by the solution concentration.
[0026] Preferably, in the method of the present invention, the carbon slurry comprises flake graphite, conductive carbon powder and a high boiling point solvent. The present invention does not specifically limit the carbon slurry, and conventional carbon slurry in the art can be used.
[0027] Preferably, in the method of the present invention, the high boiling point solvent is polyacrylate.
[0028] Preferably, in the method of the present invention, the first organic solvent is selected from one or more of ethanol, methanol, isopropanol and acetone.
[0029] Preferably, in the method of the present invention, the heat treatment in step (3) is carried out under the following conditions: the heat treatment temperature is 60-120° C., and the heat treatment time is 8-30 minutes.
[0030] In a third aspect, the present invention provides the use of the flexible composite electrode of the present invention or the flexible composite electrode prepared by the method of the present invention in a perovskite solar cell.
[0031] In a fourth aspect, the present invention provides a perovskite solar cell, comprising a transparent substrate, a conductive layer, an electron transport layer, a perovskite light absorbing layer, an optional hole transport layer, and a flexible composite electrode stacked in sequence from bottom to top; wherein the flexible composite electrode is the flexible composite electrode of the present invention or a flexible composite electrode obtained by the method of the present invention.
[0032] Preferably, in the perovskite solar cell described in the present invention, the perovskite solar cell is a positive-type perovskite solar cell.
[0033] In a specific embodiment of the present invention, the present invention provides a method for preparing a flexible composite electrode, which comprises the following steps:
[0034] (1) coating the carbon slurry on a flexible conductive substrate to obtain a wet film;
[0035] (2) Soaking the obtained wet film in ethanol for a period of time and drying it with nitrogen to obtain a flexible electrode;
[0036] (3) Depositing a layer of modification material on the surface of the flexible electrode by spin coating or scraping;
[0037] (4) Heating on a low-temperature hot plate to obtain the final flexible composite electrode.
[0038] In a specific embodiment of the present invention, the carbon slurry is a mixture (ground) of flake graphite, conductive carbon powder and polyacrylate.
[0039] In the method of the present invention, the flexible conductive substrate includes ITO / PET, ITO / PEN, Ag NWs / PET (NWs, nanowires), Ag NPs / PET (NPs, nanoparticles) or CNTs / PET (CNTs, carbon nanotubes).
[0040] In a specific embodiment of the present invention, the carbon slurry is coated on a flexible conductive substrate by a doctor blade coating method to obtain a wet film.
[0041] In a specific embodiment of the present invention, the wet film is immersed in ethanol for about 20 minutes and blown dry with nitrogen to obtain a flexible electrode.
[0042] In a specific embodiment of the present invention, a small-area modified material film is obtained by spin coating, and a large-area modified material film is obtained by blade coating. The film-forming conditions of the spin coating method are 2000-4000 rpm, 15-60 seconds; the film-forming conditions of the blade coating method are: the solution dosage is 100-200 μl, and the coating speed is 2-8 mm·s -1 , apply 1 to 3 times.
[0043] In a specific embodiment of the present invention, the wet film is heated on a hot plate at 80° C. for 10 minutes to remove the organic solvent.
[0044] The present invention also provides a perovskite solar cell. The perovskite solar cell can be obtained by a method comprising the following steps:
[0045] (1) Etching and cleaning of transparent conductive substrates;
[0046] (2) Depositing an electron transport layer on a transparent conductive substrate (see Joule, 2022, 6, 676-689; Nature Photonics, 2019, 13, 460-466.);
[0047] (3) Perovskite thin film deposition;
[0048] (4) Deposition of hole transport layer;
[0049] (5) laminating the flexible composite electrode of the present invention to the perovskite light absorbing layer or the perovskite light absorbing layer / hole transport layer by hot pressing;
[0050] (6) Assemble into a complete battery.
[0051] Preferably, in the method described in the present invention, the transparent conductive substrate comprises FTO conductive glass, ITO conductive glass, flexible ITO / PET, or flexible ITO / PEN.
[0052] Preferably, in the method of the present invention, the electron transport layer comprises TiO 2 or SnO 2 , using a film thickness in the range of 15 to 30 nm.
[0053] Preferably, in the method of the present invention, the perovskite light absorbing layer comprises MAPbI 3 , FAPbI 3 , Cs x MA y FA 1-x-y PbI 3 (x=0~0.15, y=0~0.15), Rb x MA y FA 1-x-y PbI 3 (x=0~0.15, y=0~0.15), Cs x MA y FA 1-x-y PbB m I 3-m (x=0~0.15, y=0~0.15, m=0~0.15), CsPbI 3 , or CsPb(I, Br) 3 , the film thickness is in the range of 300 to 1000 nm.
[0054] Preferably, in the method of the present invention, the hole transport layer comprises spiro-OMeTAD and PTAA, and the film thickness is in the range of 80 to 100 nm.
[0055] Preferably, in the method of the present invention, a small-area thin film (including an electron transport layer, a perovskite light absorption layer, and a hole transport layer) is obtained by spin coating, and a large-area thin film is obtained by blade coating. The preparation conditions of the spin coating method are 2000-4000 rpm, 15-60 seconds; the film scraping conditions of the blade coating method are: the solution dosage is 100-200 μl, and the coating speed is 2-8 mm·s -1 , apply 1 to 3 times.
[0056] The flexible composite electrode provided by the present invention is mainly developed to address the interface contact problem between the carbon electrode and the perovskite layer or the perovskite layer / hole transport layer. By modifying the material layer, not only can the interface contact performance be further improved, but also the conductivity, interface charge transfer rate and hole extraction efficiency of the flexible electrode can be improved. Therefore, the flexible composite electrode of the present invention can significantly improve the conversion efficiency and stability of the perovskite solar cell. In addition, compared with the existing method for preparing perovskite thin-film solar cells, the present invention also has the following beneficial effects:
[0057] 1) The production process is simple and easy, and the film thickness is easy to control;
[0058] 2) The preparation cost is significantly reduced;
[0059] 3) This method is suitable for preparing large-area perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0061] Figure 1 This is a front SEM image of the flexible composite electrode prepared in Example 4 of the present invention;
[0062] Figure 2 This is a cross-sectional SEM image of the flexible composite electrode prepared in Example 4 of the present invention;
[0063] Figure 3 It is a schematic structural diagram of a perovskite-based thin-film solar cell based on a flexible composite electrode according to a specific embodiment of the present invention. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0065] The inventors of the present invention have found through in-depth research on the interface problems related to flexible perovskite solar cells and carbon-based perovskite solar cells that the interface contact problem between the flexible carbon electrode and the perovskite or the perovskite / hole transport layer has a very huge impact on the battery performance. The main reason is that most carbon electrodes require high-temperature annealing during the preparation process, but for flexible electrodes, high-temperature annealing cannot be performed. Therefore, the interface contact between the flexible electrode and the perovskite or the perovskite / hole transport layer has always been a big problem, and the carbon-based flexible electrode itself has poor conductivity, which is not conducive to the rapid extraction and transmission of holes. Therefore, it is very necessary to modify the surface interface of the flexible electrode, which is conducive to improving the efficiency of the perovskite battery.
[0066] Figure 1 This is a front SEM image of the flexible composite electrode prepared in Example 4 of the present invention. Figure 2 This is a cross-sectional SEM image of the flexible composite electrode obtained in Example 4 of the present invention. Figure 1 and Figure 2 It can be seen that the carbon film has a macroporous structure, which will deform to a certain extent under the action of external force and show flexible characteristics.
[0067] The invention also provides a titanite solar cell. Figure 3 Schematic diagram of the structure of a perovskite battery provided according to one embodiment of the present invention. Figure 3 As shown, the perovskite solar cell 100 includes a transparent substrate 101, a conductive layer 102, an electron transport layer 103, a perovskite light absorption layer 104, a hole transport layer 105, and a flexible composite electrode 107 arranged from bottom to top; wherein the flexible composite electrode 107 includes a flexible conductive substrate, a conductive carbon layer and a modification material layer (i.e., an interface modification layer).
[0068] The various structural layers of the flexible perovskite solar cell 100 are described in detail below.
[0069] The transparent substrate 101 is made of glass, PET (polyethylene terephthalate) or PEN (polyethylene naphthalate diformic glycol ester).
[0070] The conductive layer 102 is an ITO (Indium tin oxide) or FTO (Fluorine-doped tinoxide) layer. The flexible transparent substrate 101 and the conductive layer 102 together constitute a transparent conductive substrate (abbreviated as ITO glass, FTO glass, ITO / PET, ITO / PEN). Before preparing the battery, it is first necessary to use P1 to etch one or more insulating strips on the transparent conductive substrate to form one or more non-conductive areas on the conductive glass (P1 etching is performed using a method known in the art, refer to Adv. Energy Mater. 2022, 2202287.)
[0071] The electron transport layer 103 is TiO 2 or SnO 2 Among them, TiO can be used on FTO glass 2 or SnO 2 Layer, SnO on ITO / PET and ITO / PEN 2 Layer. Among them, SnO 2 The layer is made by spin coating or blade coating of nanocrystalline SnO 2 The film thickness is in the range of 15-30 nm. Before use, it needs to be heat treated. SnO 2 Layer annealing temperature 170℃, TiO 2 The annealing temperature of the layer is 500°C. 2 Let me give you an example to illustrate this.
[0072] The perovskite light absorbing layer 104 is MAPbI 3 , FAPbI 3 , Cs x MA y FA 1-x-y PbI 3 (x=0~0.15, y=0~0.15), Rb x MA y FA 1-x-y PbI 3 (x=0~0.15, y=0~0.15), Cs x MA y FA 1-x-y PbB m I 3-m (x=0~0.15, y=0~0.15, m=0~0.15), CsPbI 3 , or CsPb(I, Br) 3 , the film thickness is about 700 nm.
[0073] Small-area and large-area perovskite films were obtained by spin coating and blade coating, respectively. The film-forming conditions of the spin coating method were 3000 rpm and 30 seconds; the film-forming conditions of the blade coating method were: solution volume 100-200 μl, coating speed 5 mm·s -1 , coated once; the wet film was annealed on a hot plate at 110 degrees for 30 minutes.
[0074] The hole transport layer 105 includes spiro-OMeTAD (2,2′,7,7′-tetrakis(N,N-dimethoxyphenylamine)-9,9′-spirobifluorene) and PTAA (poly[bis(4-phenyl)(2, 4,6-trimethylphenyl)amine]), and the film thickness is in the range of 80 to 100 nm. The small-area and large-area hole transport layers are obtained by spin coating and blade coating, respectively. The film-forming conditions of the spin coating method are 3000 rpm and 30 seconds; the film-forming conditions of the blade coating method are: the solution dosage is 100 to 200 μl, and the coating speed is 5 mm·s -1 , apply once.
[0075] The flexible composite electrode 107 is based on a carbon electrode. The carbon slurry is directly scraped onto a flexible conductive substrate to obtain a wet carbon film, which is then soaked in ethanol for about 20 minutes and dried with nitrogen to obtain a substrate with a conductive carbon layer having a thickness of 1 to 50 μm. Flexible conductive substrates include ITO / PET, ITO / PEN, Ag NWs / PET (NWs, nanowires), Ag NPs / PET (NPs, nanoparticles), CNTs / PET (CNTs, carbon nanotubes), and the like. The carbon slurry is a mixture of flaky graphite, conductive carbon powder, and polyacrylate. In the embodiment, the amounts of flaky graphite, conductive carbon powder, and polyacrylate are flaky graphite (1.4 g), conductive carbon powder (1.6 g), and polyacrylate (4.5 g), respectively, as examples.
[0076] The modified material layer (i.e., interface modified layer) includes carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole, polyaniline, etc. The solvent used is one or more of ethanol, methanol, isopropanol, acetonitrile, etc., but not limited thereto. The concentration range of the modified material slurry is 0.1-20 mM. Since the thickness of the modified material layer is extremely thin, the relative thickness is expressed by the solution concentration. The modified material slurry is deposited on the conductive carbon layer by spin coating or blade coating, and then heated at 80°C on a low temperature hot stage for 10 minutes to obtain a flexible composite electrode.
[0077] Finally, the flexible composite electrode was bonded together with the perovskite layer / hole transport layer by hot pressing to obtain a complete perovskite cell; the hot pressing temperature was 60°C and the pressure was 0.5 MPa.
[0078] It should be noted that for perovskite solar cells, the most important parameter is the cell conversion efficiency. The higher the cell conversion efficiency, the better the performance of the perovskite solar cell. In addition, it is well known in the art that the four parameters for evaluating cell performance, Jsc (short circuit current density), Voc (open circuit voltage), FF (fill factor) and Eff. (cell conversion efficiency), have the following relationship: Eff. = (Jsc×Voc×FF) / P in (P in : The intensity of incident sunlight. Under standard 1 sun, the intensity is 100 mW / cm 2 ).
[0079] Examples 1-9
[0080] On the ITO / PET substrate, a conductive carbon layer was prepared, and carbon quantum dots were deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm, and the concentration of carbon quantum dots was 0.1 to 20 mM. At the same time, on the FTO conductive glass (101 / 102), the electron transport layer (103) was SnO 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 (thickness is about 700 nm), the hole transport layer (105) is spiro-OMeTAD (thickness is about 80 nm), and it is assembled with the flexible composite electrode into a positive perovskite solar cell (cell area is 1 cm 2 ).
[0081] Table 1 lists the specific experimental parameters of the perovskite solar cells prepared in Examples 1-9.
[0082] Table 1
[0083] Serial number Modification Materials Concentration of modified material (mM) <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 1 Carbon Quantum Dots 0 24.2 1162 0.72 20.25 1 Example 2 Carbon Quantum Dots 0.1 25.0 1179 0.78 23.50 1 Example 3 Carbon Quantum Dots 0.5 24.9 1195 0.80 23.80 1 Example 4 Carbon Quantum Dots 1.0 25.1 1210 0.83 25.21 1 Example 5 Carbon Quantum Dots 2.0 24.8 1206 0.81 24.23 1 Example 6 Carbon Quantum Dots 5 24.8 1191 0.79 23.33 1 Example 7 Carbon Quantum Dots 10 24.8 1182 0.76 22.28 1 Example 8 Carbon Quantum Dots 20 24.7 1175 0.76 22.06 1 Example 9 Carbon Quantum Dots 22 24.9 1170 0.75 21.85 1
[0084] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0085] Examples 10-13
[0086] Conductive carbon layers were prepared on different flexible substrates, and a carbon quantum dot solution with a concentration of 1.0 mM was deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm. At the same time, on the FTO conductive glass (101 / 102), the electron transport layer (103) was SnO 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 (thickness is about 700 nm), the hole transport layer (105) is spiro-OMeTAD (thickness is about 80 nm), and it is assembled with the flexible composite electrode into a positive perovskite solar cell (cell area is 1 cm 2 ).
[0087] Table 2 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 10-13.
[0088] Table 2
[0089] Serial number Flexible electrode substrate <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 4 ITO / PET 25.1 1210 0.83 25.21 1 Example 10 ITO / PEN 24.6 1208 0.80 23.77 1 Embodiment 11 Ag NWs / PET 24.8 1200 0.77 23.97 1 Example 12 Ag NPs / PET 24.7 1198 0.78 23.08 1 Embodiment 13 CNTs / PET 24.8 1205 0.81 24.21 1
[0090] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0091] Examples 14-16
[0092] On the ITO / PET substrate, a conductive carbon layer was prepared, and a carbon quantum dot solution with a concentration of 1.0 mM was deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm. 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 (thickness is about 700 nm), the hole transport layer (105) is spiro-OMeTAD (thickness is about 80 nm), and it is assembled with the flexible composite electrode into a positive perovskite solar cell (cell area is 1 cm 2 ).
[0093] Table 3 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 14-16.
[0094] Table 3
[0095] Serial number Transparent conductive substrate for batteries <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 4 FTO glass 25.1 1210 0.83 25.21 1 Embodiment 14 ITO glass 24.7 1208 0.80 23.87 1 Embodiment 15 ITO / PET 24.5 1205 0.82 24.21 1 Example 16 ITO / PEN 24.4 1211 0.81 23.93 1
[0096] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0097] Examples 17-21
[0098] On the ITO / PET substrate, a conductive carbon layer was prepared, and a carbon quantum dot solution with a concentration of 1.0 mM was deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm. At the same time, on the FTO conductive glass (101 / 102), an electron transport layer (103) was SnO 2 The perovskite light absorbing layer (104) with different components and a thickness of about 700 nm was used, and the hole transport layer (105) was spiro-OMeTAD (thickness of about 80 nm). The perovskite solar cells (cell area of 1 cm) were assembled with flexible composite electrodes. 2 ).
[0099] Table 4 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 17-21.
[0100] Table 4
[0101] Serial number Perovskite layer <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 4 <![CDATA[Cs 0.03 FA 0.97 PbI 3 ]]> 25.1 1210 0.83 25.21 1 Embodiment 17 <![CDATA[FAPbI 3 ]]> 25.2 1205 0.81 24.60 1 Embodiment 18 <h2 style=";text-align:left;direction:ltr"><![CDATA[Cs <h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> MA<h2 style=";text-align:left;direction:ltr"> 0.03 <h2 style=";text-align:left;direction:ltr"> FA<h2 style=";text-align:left;direction:ltr"> 0.94 <h2 style=";text-align:left;direction:ltr"> PbI<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> 25.0 1198 0.81 24.26 1 Embodiment 19 <![CDATA[MA 0.05 FA 0.95 PbI 2.97 Br 0.03 ]]> 24.6 1188 0.80 23.38 1 Embodiment 20 <![CDATA[CsPbI 3 ]]> 20.5 1220 0.84 21.01 1 Embodiment 21 <![CDATA[Cs 0.1 MA 0.3 FA 0.6 PbI 2.97 Br 0.03 ]]> 24.5 1212 0.80 23.76 1
[0102] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0103] Examples 22-26
[0104] On the ITO / PET substrate, a conductive carbon layer was prepared, and a carbon quantum dot solution with a concentration of 1.0 mM was deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was 1 to 50 μm. At the same time, on the FTO conductive glass (101 / 102), an electron transport layer (103) was SnO 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 , with a thickness of about 700 nm, and a hole transport layer (105) of spiro-OMeTAD (thickness of about 80 nm), which was assembled with a flexible composite electrode into a positive perovskite solar cell (cell area of 1 cm 2 ).
[0105] Table 5 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 22-26.
[0106] Table 5
[0107] Serial number Conductive carbon layer thickness <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 4 30 25.1 1210 0.83 25.21 1 Embodiment 22 1 24.3 1165 0.70 19.82 1 Embodiment 23 10 24.6 1182 0.75 21.81 1 Embodiment 24 20 24.8 1204 0.80 23.89 1 Embodiment 25 40 24.7 1205 0.82 24.41 1 Embodiment 26 50 24.5 1190 0.77 22.45 1
[0108] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0109] Examples 27-32
[0110] On the ITO / PET substrate, a conductive carbon layer was prepared, and different modified carbon materials with a concentration of 1.0 mM were deposited on the conductive carbon layer by spin coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm. At the same time, on the FTO conductive glass (101 / 102), the electron transport layer (103) was SnO 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 , with a thickness of about 700 nm, and a hole transport layer (105) of spiro-OMeTAD (thickness of about 80 nm), which was assembled with a flexible composite electrode into a positive perovskite solar cell (cell area of 1 cm 2 ).
[0111] Table 6 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 27-32.
[0112] Table 6
[0113] Serial number Modification Materials <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Example 4 Carbon Quantum Dots 25.1 1210 0.83 25.21 1 Embodiment 27 Single-walled carbon nanotubes 24.9 1185 0.81 23.90 1 Embodiment 28 Multi-walled carbon nanotubes 24.7 1196 0.80 23.63 1 Embodiment 29 Graphene 25.2 1206 0.82 24.92 1 Embodiment 30 Graphene oxide 25.0 1187 0.78 23.15 1 Embodiment 31 Polypyrrole 24.4 1193 0.75 21.83 1 Embodiment 32 Polyaniline 24.0 1164 0.68 19.00 1
[0114] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0115] Examples 33-35
[0116] On the ITO / PET substrate, a conductive carbon layer was prepared, and carbon quantum dots with a concentration of 1.0 mM were coated on the conductive carbon layer by blade coating to obtain a modified flexible composite electrode. The thickness of the conductive carbon layer was about 30 μm, and flexible electrodes with different areas could be obtained. 2 (thickness is 15nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 , with a thickness of about 700 nm, and a hole transport layer (105) of spiro-OMeTAD (thickness of about 80 nm), which is assembled with a flexible composite electrode into a positive perovskite solar cell with a cell area of 1 to 20.2 cm 2 .
[0117] Table 7 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 33-35.
[0118] Table 7
[0119] Serial number <![CDATA[Battery area (cm 2 ).]]> <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) Example 4 1 25.1 1210 0.83 25.21 Embodiment 33 6.4 24.4 4.820 0.77 22.64 Embodiment 34 12.4 24.2 6.035 0.71 20.74 Embodiment 35 20.2 23.9 9.626 0.64 18.40
[0120] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0121] Examples 36-37
[0122] Examples 36-37 show that for other conventional materials such as electron transport materials such as TiO 2 , experimental data when the hole transport material is PTAA, other functional layers and battery preparation are as described above, including: preparing a conductive carbon layer on an ITO / PET substrate, coating the conductive carbon layer with a concentration of 1.0 mM by spin coating, and obtaining a modified flexible composite electrode, the thickness of the conductive carbon layer is about 30 μm. At the same time, on the FTO conductive glass (101 / 102), the electron transport layer (103) is TiO 2 (thickness is 15 nm), the perovskite light absorbing layer (104) is Cs 0.03 FA 0.97 PbI 3 , with a thickness of about 700 nm, and a hole transport layer (105) of PTAA (thickness of about 80 nm), which is assembled with a flexible composite electrode into a positive perovskite solar cell with a cell area of 1 cm 2 .
[0123] Table 8 gives the specific experimental parameters of the perovskite solar cells prepared in Examples 36-37.
[0124] Table 8
[0125] Serial number Carrier transport layer <![CDATA[Jsc(mA cm -2 )]]> Voc(mV) FF Eff.(%) <![CDATA[Battery area (cm 2 ).]]> Embodiment 36 <![CDATA[TiO 2 / spiro-OMeTAD]]> 24.8 1195 0.80 23.71 1 Embodiment 37 <![CDATA[SnO 2 / PTAA]]> 25.0 1201 0.81 24.32 1
[0126] Among them, Jsc: short-circuit current density; Voc: open-circuit voltage; FF: fill factor; Eff.: battery conversion efficiency.
[0127] In summary, it can be seen from Examples 1-37 that the perovskite solar cell based on the flexible composite electrode of the present invention can achieve a higher photoelectric conversion efficiency; and this flexible electrode can be used to prepare perovskite cells of different areas. In addition, the preparation process of the present invention is simple and low in cost, which can meet commercial requirements.
[0128] At this point, those skilled in the art should recognize that, although multiple exemplary embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the content disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all these other variations or modifications.
Claims
1. A flexible composite electrode, include: Flexible conductive substrate, a conductive carbon layer located on the flexible conductive substrate; as well as a modification material layer located on the conductive carbon layer; Wherein, the modified material layer is composed of one or more materials selected from carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole and polyaniline.
2. The flexible composite electrode according to claim 1, in, The thickness of the conductive carbon layer is 1 to 50 μm; Preferably, the flexible conductive substrate is ITO / PET, ITO / PEN, Ag nanowire / PET, Ag nanoparticle / PET, or carbon nanotube / PET.
3. A method for preparing a flexible composite electrode according to any one of claims 1 to 2, wherein The following steps are involved: (1) coating a carbon slurry on a flexible conductive substrate to obtain a substrate with a carbon slurry coating; (2) immersing the substrate with the carbon slurry coating in a first organic solvent to remove the high boiling point solvent in the carbon slurry coating, and obtaining a substrate with a conductive carbon layer after drying; (3) coating the modified material dispersion on the conductive carbon layer, and subjecting the obtained structure to a heat treatment to remove all organic solvents, thereby obtaining a flexible composite electrode.
4. The method according to claim 3, in, The modifying material dispersion comprises a modifying material and a second organic solvent; The modified material is selected from one or more of carbon quantum dots, single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphene oxide, polypyrrole and polyaniline; The second organic solvent is selected from one or more of ethanol, methanol, isopropanol and acetonitrile.
5. The method according to claim 3, in, The concentration of the modified material dispersion is 0.1-20 mM.
6. The method according to claim 3, in, The carbon slurry comprises flake graphite, conductive carbon powder and a high boiling point solvent; Preferably, the high boiling point solvent is polyacrylate; Preferably, the first organic solvent is selected from one or more of ethanol, methanol, isopropanol and acetone.
7. The method according to claim 3, in, The heat treatment in step (3) is carried out under the following conditions: the heat treatment temperature is 60-120° C., and the heat treatment time is 8-30 minutes.
8. Use of the flexible composite electrode according to any one of claims 1 to 2 or the flexible composite electrode prepared by the method according to any one of claims 3 to 7 in a perovskite solar cell.
9. A perovskite solar cell comprising a transparent substrate, a conductive layer, an electron transport layer, a perovskite light absorbing layer, an optional hole transport layer, and a flexible composite electrode stacked sequentially from bottom to top; in, The flexible composite electrode is the flexible composite electrode according to any one of claims 1 to 2 or the flexible composite electrode prepared by the method according to any one of claims 3 to 7. 10 . The perovskite solar cell according to claim 9 , wherein the perovskite solar cell is a positive-type titanite solar cell.
